The ABA Method Assisted by Picture Card Media to Improve the Speaking Ability of Group B Children with Autism - A'isyah Nirna Wati; Luh Ayu Tirtayani (Universitas Pendidikan Ganesha, 2023)
Treatment options for ASD include Applied Behavior Analysis (ABA) based on learning theory and operant conditioning. Picture cards are an effective medium for object identification for autistic children. This study aims to analyze the effect of the Application of the ABA Method assisted by Picture Card Media on the speaking abilities of students with autism. This type of research is a single-case experimental design which was carried out in three phases, namely the baseline phase (A1), the intervention phase (B) and the baseline phase (A2). The subjects in this study were two children of group B. The collection of research data on the speaking ability of students with autism used observation and interview methods with an observation checklist sheet instrument. Research data were analyzed using descriptive statistical analysis methods and data presentation was presented visually (visual inspection) in graphical form. The results of data analysis showed that there was a decrease in the frequency of speaking ability and an increase in the frequency of speaking ability from the baseline phase (A1) with an average of 6 to 14.18 in the intervention phase (B) and an increase in the frequency of speaking skills of students with autism during the ABA approach intervention with the help of media picture cards in learning stopped (A2) with an average of 18.7. Based on the results of this study it can be concluded that the ABA method approach with the help of picture card media in learning the speaking skills of students with autism Group B.